2016
DOI: 10.1002/eji.201546179
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated expansion of both memory T cells and NK cells in response to CMV infection in humans

Abstract: NK cells are key players in the fight against persistent viruses. Human cytomegalovirus (HCMV) infection is associated with the presence of a population of CD16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…Previously published data [21][22] have shown that high CD57 expression levels, co-expressed with NKG2C, on CD56 dim NK cells, define a terminal maturational step for CD56 dim NK cells and depict a human viral memory NK cell subset, which lacks in NK cells derived from patients with mutations in NFKB1. Exposure to CMV has been shown to up-regulate CD57 and NKG2C on human NK cells [23][24]. Within this cohort of patents, only one patient presented an infection from CMV.…”
Section: Discussionmentioning
confidence: 90%
“…Previously published data [21][22] have shown that high CD57 expression levels, co-expressed with NKG2C, on CD56 dim NK cells, define a terminal maturational step for CD56 dim NK cells and depict a human viral memory NK cell subset, which lacks in NK cells derived from patients with mutations in NFKB1. Exposure to CMV has been shown to up-regulate CD57 and NKG2C on human NK cells [23][24]. Within this cohort of patents, only one patient presented an infection from CMV.…”
Section: Discussionmentioning
confidence: 90%
“…There seem to be limited age-related changes in KIR and NKG2 repertoires of NK cells. A decrease in NKG2A expression occurs from young to elderly adults [104,105]. In contrast, an increased frequency of KIR expression was observed in NK cells from cord blood to adults without any further increases in the elderly [98].…”
Section: Natural Killer Cells: Changes In Their Subsetsmentioning
confidence: 86%
“…Indeed, highly differentiated mature CD57 C CD56 C CD16 C NK cells accumulated with aging (in particular in CMV seropositive donors). [56][57][58] In HIV patients, it is their functionality which is modified: these cells display a decreased ability to kill virus-infected target cells and to interact with other cellular components of the adaptive immune system. 59,60 During chronic HIV infection, there is an impairment of NK cell cytotoxicity and cytokine secretion as well as a reduced capacity to respond to IFN-a and to produce high amounts of IFN-g and TNF a along with low amounts of perforin.…”
Section: Gradual Loss Of the Cd56mentioning
confidence: 99%